2006
DOI: 10.1107/s1600536806020575
|View full text |Cite
|
Sign up to set email alerts
|

Redetermination and H-atom refinement of (S)-(+)-ibuprofen. Corrigendum.

Abstract: Key indicatorsSingle-crystal X-ray study T = 298 K Mean (C-C) = 0.005 Å R factor = 0.038 wR factor = 0.104 Data-to-parameter ratio = 7.0 For details of how these key indicators were automatically derived from the article, see

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…This result is consistent with the reported structures of racemic and nonracemic crystalline ibuprofen in which the molecules form hydrogen-bonded cyclic dimers. 37,53,54 Moreover, these cyclic structures are found to be extremely stable compared to the linear ones. Indeed, the survival probability of the intermolecular HBs structures formed between the different ibuprofen molecules has been estimated from the time decay of the intermittent correlation function C n (t) ) 〈h n (t) • h n (0)〉 where h n (t) is unity if a given multimer composed of n molecules formed at time 0 remains intact at time tseven if it has broken in betweensand is zero otherwise.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…This result is consistent with the reported structures of racemic and nonracemic crystalline ibuprofen in which the molecules form hydrogen-bonded cyclic dimers. 37,53,54 Moreover, these cyclic structures are found to be extremely stable compared to the linear ones. Indeed, the survival probability of the intermolecular HBs structures formed between the different ibuprofen molecules has been estimated from the time decay of the intermittent correlation function C n (t) ) 〈h n (t) • h n (0)〉 where h n (t) is unity if a given multimer composed of n molecules formed at time 0 remains intact at time tseven if it has broken in betweensand is zero otherwise.…”
Section: Resultsmentioning
confidence: 98%
“…This result is consistent with the estimation of a weak dipole moment from the ab initio calculations 40 of the isolated racemic (0.00 D) and nonracemic (0.54 D) cyclic dimers as found in crystalline ibuprofen. 37,53,54 However, the values of the dipole moment of the cyclic dimers obtained in the disordered phase (50:50 mixture of racemic/ nonracemic) are significantly higher than that for crystalline one since the structures might have distorted geometries.…”
Section: Table 2: Estimated Parameters Of the Arrhenius Fit τ(T) ) τ ...mentioning
confidence: 96%
“…The chiral behavior of the ibuprofen free acid has been the subject of numerous studies, and it has been reported that the racemic compound or “true racemate” (“any homogeneous solid composed of equimolar amounts of enantiomeric molecules”, following the IUPAC rule) is much more stable than the corresponding racemic conglomerate (or racemic mixture, that is, “a mixture of equimolar amounts of enantiomeric molecules present as separate solid phases”, following the IUPAC rule). In particular, the true racemate form is the only stable solid form, and, as a consequence, ( R , S )-ibuprofen has a dimorphic (true racemate/conglomerate) behavior of the monotropic type …”
Section: Introductionmentioning
confidence: 99%
“…A sodium salt of a well-known racemic active pharmaceutical ingredient (API), (R,S)-(()-ibuprofen ((R,S)-(()-2-(4-isobutylphenyl)propionic acid) was chosen as a model system because of its parent acid (R,S)-(()-ibuprofen's worldwide commercial values in analgesic, anti-inflammatory, and antipyretic therapy 20 and (2) its abundant information in the literature. [21][22][23][24][25][26][27][28][29][30][31][32][33] It is known that (S)-(+)-ibuprofen is the active agent and (R)-(-)-ibuprofen is partially converted into (S)-(+)-ibuprofen in humans. Therefore, ibuprofen is marketed as a racemic compound.…”
Section: Introductionmentioning
confidence: 99%